Porous alpha-Al2O3 ceramic microbead material and preparation method thereof

Through the drip instillation method combined with sintering process, combined with PB sol and alginic acid sol, Al2O3 ceramic microbeads with high strength and porous structure were prepared, which solved the mechanical dependence and strength problems in the traditional method, achieved the preparation of ceramic microbeads with high spherical shape and adjustable pore size, and showed good adsorption performance.

CN119841629APending Publication Date: 2025-04-18TIANJIN CHENGJIAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901534.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art has problems of mechanical dependence, path dependence and size dependence in the preparation of spherical Al2O3 ceramic microbeads, and it is difficult to solve the problems of strength and stability while retaining adjustable pore size and high spherical shape in the field of catalyst support.

Method used

Al2O3 ceramic microbeads with porous structure were prepared by combining the PB sol with an alginic acid sol using a drop infusion method combined with a sintering process. This method simplifies the ceramic preparation process, reduces the sintering temperature, and increases the strength of the ceramic through TEOS immersion treatment.

Benefits of technology

The prepared Al2O3 ceramic microbeads have high strength, high porosity, and exhibit good methylene blue (MB) adsorption performance, and can achieve reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841629A_ABST
    Figure CN119841629A_ABST
Patent Text Reader

Abstract

The invention relates to a porous alpha-Al2O3 ceramic microbead material and a preparation method thereof, belongs to the field of preparation of chemical materials, and solves the problems of complicated forming and difficult sintering of porous Al2O3 ceramic microbeads at present. Pseudo-boehmite (PB) and Al2O3 are mainly used as basic raw materials and are simply dripped into a solution containing Ca < 2 + > to form hydrogel, and after drying, the hydrogel is prepared by combining a sintering process. By regulating and controlling the raw material ratio, the Ca < 2 + > concentration and the drying mode, the porous microbeads with controllable diameters and the porosity reaching 65% or above can be obtained. The porous alpha-Al2O3 ceramic microbead material has good adsorbability to methylene blue (MB) dye, and the dye can be removed after being subjected to heat treatment at 500 DEG C for multiple times, so that the material can be recycled. According to the invention, a new thought is provided for the preparation of Al2O3 ceramic by converting the pseudo-boehmite into the alpha-Al2O3, and the prepared alpha-Al2O3 ceramic microbead material can be used as a specific dye pollutant adsorption material and also has the potential of being used as a catalyst carrier material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical material preparation, and specifically relates to a porous α-Al2O3 ceramic microbead material and a preparation method thereof. The material is prepared by a simple dripping method combined with a sintering process, and has broad application prospects in dye pollutant wastewater treatment and catalyst carrier material treatment of gaseous waste. Background Art

[0002] Porous ceramic microbeads have great application potential in catalysis, drug sustained release, etc. due to their excellent acid and alkali resistance, chemical stability, mechanical strength and other advantages. Their spherical shape provides good fluidity and high density, making them easy to separate and regenerate for reuse. Traditional spherical Al2O3 ceramic preparation methods such as rolling molding, mechanical ball forming, template method and other processes have problems of mechanical dependence, path dependence and size dependence. Seeking a simple and non-toxic preparation method to obtain Al2O3 ceramic microbeads with good sphericity and controllable structure has become a research focus.

[0003] Sodium alginate (SA) is a natural polymer material that can react with divalent or trivalent cations (such as Ca 2+ 、Al 3 + , Fe 3+ etc.) to react to form a gel with an "egg box" structure. Taking advantage of the spherical properties of alginate, eggshell straw biochar composite microspheres have been prepared as phosphorus removal adsorbents, graphene-modified calcium alginate microbial curing agents, etc., but there are few reports on their preparation in the ceramic field. The single calcium alginate gel, namely the CA gel network, has the disadvantages of a loose network structure and low strength, and is prone to large shrinkage during the drying and sintering process, resulting in cracking of the microbeads, which reduces the strength of the ceramic. In addition, in the field of catalyst carriers, surface tension is often used. In an oil-water network, interfacial tension is used to rapidly shrink the sol droplets into a sphere, and then an initiator is added to promote its curing to prepare alumina ceramic microbeads. However, the curing process is relatively complicated, and some large equipment is required, resulting in high costs. PB (pseudo-boehmite) material in H + Peptization γ -AlOOH hydrosol is an important raw material for the sol-gel process to form Al2O3. It can significantly reduce the sintering temperature of Al2O3 materials, but it is difficult to prepare spherical Al2O3. How to solve the problems of strength and stability while retaining the advantages of spherical Al2O3 with adjustable pore size and high sphericity is still a difficulty in current research.

[0004] The present invention adopts the dripping method to prepare Al2O3 ceramic microbeads, which has the characteristics of simple preparation and strong particle size adjustability. At the same time, the PB sol and the alginate sol are combined to reduce the sintering temperature of the material while ensuring the ball formation, and simplify the ceramic preparation process. The results show that the Al2O3 ceramic microbeads have high strength and porosity, and show good adsorption performance for MB, and can be reused. Summary of the invention

[0005] The present invention provides a porous α-Al2O3 ceramic microsphere material and a preparation method thereof. The specific preparation steps are as follows:

[0006] (1) A certain proportion of PB and Al2O3 powder was dissolved in 20 mL of water, and a suspension was obtained under the action of citric acid as a dispersant and ultrasonic conditions. SA was then added to prepare a mixed slurry, and magnetic stirring was performed for 3 h, which was recorded as solution A.

[0007] (2) Prepare 50 mL of a mixed solution of CaCl2 and HCl of a certain concentration, referred to as solution B;

[0008] (3) Using droppers of different diameters, drop solution A into solution B, keeping the distance between the dropper and the liquid at about 25 cm. After the obtained hydrogel microbeads are allowed to stand and solidify for 3 hours, they are soaked in deionized water for 48 hours, during which the water is changed every 8 hours to remove excess ions, and the hydrogel microbeads are obtained after filtering with a filter;

[0009] (4) Wiping off the surface moisture, drying by different drying methods, and then sintering at 1200°C, with a heating rate of 5°C / min, keeping the temperature for 2h, and cooling with the furnace to obtain millimeter-sized Al2O3 ceramic microspheres;

[0010] (5) Preferred preparation process, pH of solution B = 5, Ca 2+ The concentration of PB is 0.8%; in solution A, the amount of PB is 3g and the amount of Al2O3 is 1g; the drying process is: after freezing at -18℃ for 12h, soaking in ethanol and tetraethyl orthosilicate (TEOS) solution for 3h respectively, and then drying at 60℃ to obtain dry gel microbeads; sintering at 1200℃, the density is 1.32g / cm 3 , the porosity is 65.21%.

[0011] This process uses a simple drip method combined with a sintering process to prepare Al2O3 ceramic microspheres. The preparation process is simple, the green body does not need to be pre-sintered and degreased, and the operation is simple and safe. This method combines the pseudo-boehmite network and the alginate-egg box structure characteristics to prepare Al2O3 ceramic microspheres with a porous structure. Ca 2+ and H +The balance of concentration plays an important role in the stable network structure of hydrogel spheres, and TEOS immersion treatment helps to improve the strength of ceramics. The density of Al2O3 ceramic microspheres is 1.32g / cm 3 , with a diameter of about 3 mm and a porosity of 65.21%, it is the first choice for the selective adsorption and recovery of methylene blue (MB). BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a process flow chart and physical picture of the preparation process of Al2O3 ceramic microbeads in Example 4.

[0013] Figure 2 It is the porosity and volume density of the Al2O3 ceramic microbead material in Examples 1-4.

[0014] Figure 3 It is a scanning electron microscope image of the Al2O3 ceramic microbead material in Examples 1-4.

[0015] Figure 4 1 is a graph showing the variation of dye adsorption rate of the Al2O3 ceramic microbead material in Examples 1-4.

[0016] Figure 5 This is the compressive strength test of the Al2O3 ceramic microbead material in Example 4. DETAILED DESCRIPTION

[0017] The present invention is further described below by specific examples and drawings. The examples of the present invention are intended to enable those skilled in the art to better understand the present invention, and do not limit the present invention in any way.

[0018] Example 1

[0019] (1) 3 g PB and 1 g Al2O3 powder were dissolved in 20 mL water, and a suspension was obtained under the action of 0.1 g citric acid as a dispersant and ultrasonic conditions. 0.2 g SA was added to prepare a mixed slurry, which was magnetically stirred for 3 h and recorded as solution A.

[0020] (2) Prepare 50 mL of a mixed solution of 0.4 g of CaCl2 and pH 2 HCl, referred to as solution B.

[0021] (3) Use a dropper with a diameter of 5 mm to drip solution A into solution B, keeping the distance between the dropper and the liquid at about 25 cm. After the obtained hydrogel microbeads are allowed to stand and solidify for 3 hours, they are soaked in deionized water for 48 hours, during which the water is changed every 8 hours to remove excess ions, and the hydrogel microbeads are obtained after filtering with a filter.

[0022] (4) Wipe off the surface moisture, freeze at -18℃ for 12h, soak in ethanol and tetraethyl orthosilicate (TEOS) solution for 3h respectively, dry at 60℃ to obtain dry gel microbeads, and then sinter at 1200℃. The heating rate is 5℃ / min, keep warm for 2h, and cool in the furnace to obtain Al2O3 ceramic microbeads. The obtained ceramic ball has a diameter of about 3mm and a density of 1.03g / cm 3 , the porosity is 74.36%. Figure 3 a It can be seen that there are pores with more interconnected channels and larger sizes inside the microbeads.

[0023] (5) 0.5 g Al2O3 ceramic microbead material was placed in 25 mL (5 mg / L) MB solution. After 24 hours, the fading rate of the dye was 6.88%.

[0024] Example 2

[0025] (1) 3 g PB and 1 g Al2O3 powder were dissolved in 20 mL water, and a suspension was obtained under the action of 0.1 g citric acid as a dispersant and ultrasonic conditions. 0.2 g SA was added to prepare a mixed slurry, which was magnetically stirred for 3 h and recorded as solution A.

[0026] (2) Prepare 50 mL of a mixed solution of 0.4 g of CaCl2 and pH 3 HCl, referred to as solution B.

[0027] (3) Use a dropper with a diameter of 5 mm to drip solution A into solution B, keeping the distance between the dropper and the liquid at about 25 cm. After the obtained hydrogel microbeads are allowed to stand and solidify for 3 hours, they are soaked in deionized water for 48 hours, during which the water is changed every 8 hours to remove excess ions, and the hydrogel microbeads are obtained after filtering with a filter.

[0028] (4) Wipe off the surface moisture, freeze at -18℃ for 12h, soak in ethanol and tetraethyl orthosilicate (TEOS) solution for 3h respectively, dry at 60℃ to obtain dry gel microbeads, and then sinter at 1200℃. The heating rate is 5℃ / min, keep warm for 2h, and cool in the furnace to obtain Al2O3 ceramic microbeads. The obtained ceramic ball has a diameter of about 3mm and a density of 1.12g / cm 3 , the porosity is 70.12%. Figure 3 b It can be seen that there are still pores with more interconnected channels and larger sizes inside the microbeads.

[0029] (5) 0.5 g of Al2O3 ceramic microbead material was placed in 25 mL (5 mg / L) MB solution. After 24 h, the fading rate of the dye was 15.63%.

[0030] Example 3

[0031] (1) 3 g PB and 1 g Al2O3 powder were dissolved in 20 mL water, and a suspension was obtained under the action of 0.1 g citric acid as a dispersant and ultrasonic conditions. 0.2 g SA was added to prepare a mixed slurry, which was magnetically stirred for 3 h and recorded as solution A.

[0032] (2) Prepare 50 mL of a mixed solution of 0.4 g of CaCl2 and pH 4 HCl, referred to as solution B.

[0033] (3) Use a 5-mm diameter dropper to drip solution A into solution B, keeping the distance between the dropper and the liquid at about 25 cm. After the obtained hydrogel microbeads are allowed to stand and solidify for 3 h, they are soaked in deionized water for 48 h, during which the water is changed every 8 h to remove excess ions. The hydrogel microbeads are then filtered through a filter to obtain the hydrogel microbeads.

[0034] (4) Wipe off the surface moisture, freeze at -18℃ for 12h, soak in ethanol and tetraethyl orthosilicate (TEOS) solution for 3h respectively, dry at 60℃ to obtain dry gel microbeads, and then sinter at 1200℃. The heating rate is 5℃ / min, keep warm for 2h, and cool in the furnace to obtain Al2O3 ceramic microbeads. The obtained ceramic ball has a diameter of about 3mm and a density of 1.23g / cm 3 , the porosity is 68.23%. Figure 3 c It can be seen that the size of the internal gap pores of the microbead material becomes smaller and the distribution becomes more uniform.

[0035] (5) 0.5 g of Al2O3 ceramic microbead material was placed in 25 mL (5 mg / L) MB solution. After 24 h, the adsorption rate of the dye was 19.23%.

[0036] Example 4

[0037] (1) 3 g PB and 1 g Al2O3 powder were dissolved in 20 mL water, and a suspension was obtained under the action of 0.1 g citric acid as a dispersant and ultrasonic conditions. 0.2 g SA was added to prepare a mixed slurry, which was magnetically stirred for 3 h and recorded as solution A.

[0038] (2) Prepare 50 mL of a mixed solution of 0.4 g of CaCl2 and pH 5 HCl, referred to as solution B.

[0039] (3) Use a dropper with a diameter of 5 mm to drip solution A into solution B, keeping the distance between the dropper and the liquid at about 25 cm. After the obtained hydrogel microbeads are allowed to stand and solidify for 3 hours, they are soaked in deionized water for 48 hours, during which the water is changed every 8 hours to remove excess ions, and the hydrogel microbeads are obtained after filtering with a filter.

[0040] (4) Wipe off the surface moisture, freeze at -18℃ for 12h, soak in ethanol and tetraethyl orthosilicate (TEOS) solution for 3h respectively, dry at 60℃ to obtain dry gel microbeads, and then sinter at 1200℃. The heating rate is 5℃ / min, keep warm for 2h, and cool in the furnace to obtain Al2O3 ceramic microbeads. The obtained ceramic ball has a diameter of about 3mm and a density of 1.32g / cm 3 , the porosity is 66.32%. Figure 3 d is the scanning electron microscope image of the Al2O3 ceramic microbead material in this example. It can be seen that the internal pore size of the microbead material is the smallest and the distribution is uniform.

[0041] (5) 0.5 g of Al2O3 ceramic microbead material was placed in 25 mL (5 mg / L) MB solution. After 24 h, the adsorption rate of the dye was 26.68%.

[0042] Figure 1 (b) is the Al2O3 dry gel microbead in this example, and (c) is the Al2O3 ceramic microbead material in this example.

[0043] Figure 5 In this example, the Al2O3 ceramic microsphere material is tested for compressive strength. A 1 kg weight is placed on top of the Al2O3 ceramic microsphere to evaluate the mechanical strength of the Al2O3 ceramic microsphere. At this time, the microsphere does not break under pressure.

[0044] Example 5

[0045] (1) 3 g PB and 0.6 g Al2O3 powder were dissolved in 20 mL water, and a suspension was obtained under the action of 0.1 g citric acid as a dispersant and ultrasonic conditions. 0.2 g SA was added to prepare a mixed slurry, which was magnetically stirred for 3 h and recorded as solution A.

[0046] (2) Prepare 50 mL of a mixed solution of 0.4 g of CaCl2 and pH 5 HCl, referred to as solution B.

[0047] (3) Use a dropper with a diameter of 5 mm to drip solution A into solution B, keeping the distance between the dropper and the liquid at about 25 cm. After the obtained hydrogel microbeads are allowed to stand and solidify for 3 hours, they are soaked in deionized water for 48 hours, during which the water is changed every 8 hours to remove excess ions, and the hydrogel microbeads are obtained after filtering with a filter.

[0048] (4) Wipe off the surface moisture, freeze at -18℃ for 12h, soak in ethanol and tetraethyl orthosilicate (TEOS) solution for 3h respectively, dry at 60℃ to obtain dry gel microbeads, and then sinter at 1200℃. The heating rate is 5℃ / min, keep warm for 2h, and cool in the furnace to obtain Al2O3 ceramic microbeads. The obtained ceramic ball has a diameter of about 3mm and a density of 1.28g / cm 3 , the porosity is 67.82%.

[0049] (5) 0.5 g of Al2O3 ceramic microbead material was placed in 25 mL (5 mg / L) MB solution. After 24 h, the adsorption rate of the dye was 23.15%.

[0050] Comparative Example 1

[0051] (1) 3 g PB and 1 g Al2O3 powder were dissolved in 20 mL water, and a suspension was obtained under the action of 0.1 g citric acid as a dispersant and ultrasonic conditions. 0.2 g SA was added to prepare a mixed slurry, which was magnetically stirred for 3 h and recorded as solution A.

[0052] (2) Prepare 50 mL of a mixed solution of 0.1 g of CaCl2 and pH 5 HCl, referred to as solution B.

[0053] (3) Use a 5 mm diameter dropper to drip solution A into solution B, keeping the distance between the dropper and the liquid at about 25 cm. At this time, no hydrogel microbeads can be obtained, and the flocculent material appears flocculent. After the obtained flocculent material is allowed to stand and solidify for 3 hours, it is continued to be soaked in deionized water for 48 hours, during which the water is changed every 8 hours to remove excess ions. The hydrogel material obtained in this example has a Ca 2+ The concentration was too low and no hydrogel microbeads were obtained, so subsequent experiments could not be performed.

[0054] Comparative Example 2

[0055] (1) 3 g PB and 1 g Al2O3 powder were dissolved in 20 mL water, and 0.1 g citric acid was used as a dispersant. The mixture was fully dispersed into a suspension under the action of ultrasound, and 0.2 g SA was added to prepare a mixed slurry. The mixture was stirred magnetically for 3 h and recorded as solution A.

[0056] (2) Prepare a mixed solution of 0.4 g of CaCl2 and HCl with a pH of 5, which is referred to as solution B.

[0057] (3) Use a 5 mm diameter rubber-tipped dropper to drip solution A into solution B, keeping the distance between the dropper and the liquid at about 25 cm. After the obtained hydrogel microbeads are allowed to stand and solidify for 3 hours, they are soaked in deionized water for 48 hours, during which the water is changed every 8 hours to remove excess ions. The hydrogel microbeads can be obtained by filtering with a filter.

[0058] (4) Wipe off the surface moisture, dry the hydrogel at room temperature and pressure, and then sinter at 1200°C. The heating rate is 5°C / min, and the temperature is kept for 2 hours. After cooling in the furnace, Al2O3 ceramic microbeads can be obtained. At this time, the microbeads have poor sphericity and are elliptical.

[0059] Comparative Example 3

[0060] (1) 3 g PB and 0 g Al2O3 powder were dissolved in 20 mL water, and 0.1 g citric acid was used as a dispersant. The mixture was fully dispersed into a suspension under the action of ultrasound, and 0.2 g SA was added to prepare a mixed slurry. The mixture was stirred magnetically for 3 h and recorded as solution A.

[0061] (2) Prepare a mixed solution of 0.4 g of CaCl2 and HCl with a pH of 5, which is referred to as solution B.

[0062] (3) Use a 5 mm diameter rubber-tipped dropper to drip solution A into solution B, keeping the distance between the dropper and the liquid at about 25 cm. After the obtained hydrogel microbeads are allowed to stand and solidify for 3 hours, they are soaked in deionized water for 48 hours, during which the water is changed every 8 hours to remove excess ions. The hydrogel microbeads can be obtained by filtering with a filter.

[0063] (4) Wipe off the surface moisture, freeze at -18°C for 12 h, soak in ethanol and tetraethyl orthosilicate (TEOS) solution for 3 h respectively, and then dry at 60°C to obtain dry gel microbeads, which are then sintered at 1200°C. At this time, the microbeads have low strength and cannot be used for subsequent experiments.

[0064] Although the preferred embodiments of the present invention are described above, the present invention is not limited to the above-mentioned specific embodiments. The above-mentioned specific embodiments are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the purpose of the present invention and the claims, which all fall within the scope of protection of the present invention.

Claims

1. A porous α-Al2O3 ceramic microsphere material and a preparation method thereof, the method comprising the following steps: Step 1: Dissolve a certain amount of PB and Al2O3 powder in 20 mL of water, use 0.1 g of citric acid as a dispersant, fully disperse into a suspension under the action of ultrasound, then add 0.2 g of SA to prepare a mixed slurry, and stir magnetically for 3 h, which is recorded as solution A; Step 2: Prepare 50 mL of a mixed solution of CaCl2 and HCl of a certain concentration, referred to as solution B; Step 3: Use a rubber-tipped dropper of different diameters to drop solution A into solution B, keeping the distance between the dropper and the liquid at about 25 cm. After the obtained hydrogel microbeads are allowed to stand and solidify for 3 hours, they are then immersed in deionized water for 48 hours. During this period, the water is changed every 8 hours to remove excess ions. The hydrogel microbeads are obtained after filtering with a filter. Step 4: Wipe off the surface moisture, dry it using different drying methods, and then sinter it at a sintering temperature of 1200℃, with a heating rate of 5℃ / min, keep it warm for 2h, and cool it with the furnace to obtain Al2O3 ceramic microbeads.

2. A porous α-Al2O3 ceramic microsphere material and a preparation method thereof according to claim 1, characterized in that: Specifically, the step 1 is as follows: 0.1-3 g PB and 2-0.6 g Al2O3 powder are dissolved in 20 mL water.

3. A porous α-Al2O3 ceramic microsphere material and a preparation method thereof according to claim 1, characterized in that: The step 2 specifically comprises preparing 50 mL of a mixed solution of 0.8-2% CaCl2 and HCl with a pH of 3-5.

4. A porous α-Al2O3 ceramic microsphere material and a preparation method thereof according to claim 1, characterized in that: The step 2 specifically comprises the following steps: freezing at -18°C for 12 hours during the drying process, soaking in ethanol and tetraethyl orthosilicate (TEOS) solution for 3 hours respectively, and then drying at 60°C to obtain dry gel microbeads; and sintering at a sintering temperature of 1200°C.

5. The Al2O3 ceramic microbeads obtained by the porous α-Al2O3 ceramic microbead material and the preparation method thereof according to claim 1 are characterized in that: Density: 1.03~1.32g / cm 3 , diameter about 1 to 7 mm, porosity 66.32% to 74.36%.

6. The Al2O3 ceramic microbeads obtained by the porous α-Al2O3 ceramic microbead material and the preparation method thereof according to claim 1 have an adsorption capacity of 26.68% for methylene blue (MB) dye after 24 hours. After 5 cycles, the adsorption performance of the microbeads has not changed significantly, and the mass loss is less than 5%.